PRO ("The Window Is Open"): In patients with cirrhosis with prior variceal hemorrhage and ascites, the clinical benefits of nonselective beta‐blockers outweigh the risks and should be prescribed. Issue 5 (5th June 2018) - Tholey, Danielle; Roth, Nitzan; Schiano, Thomas
Abstract : Watch a video presentation of this article